Smog Nitrogen and the Rapid Acidification of Forest Soil, San Bernardino Mountains, Southern California. (2007) - Wood, Yvonne A.; Fenn, Mark; Meixner, Thomas; Shouse, Peter J.; Breiner, Joan; Allen, Edith; Wu, Laosheng
Abstract : We report the rapid acidification of forest soils in the San Bernardino Mountains of southern California. After 30 years, soil to a depth of 25 cm has decreased from a pH (measured in 0.01 M CaCl2 ) of 4.8 to 3.1. At the 50-cm depth, it has changed from a pH of 4.8 to 4.2. We attribute this rapid change in soil reactivity to very high rates of anthropogenic atmospheric nitrogen (N) added to the soil surface (72 kg ha–1 year–1) from wet, dry, and fog deposition under a Mediterranean climate. Our research suggests that a soil textural discontinuity, related to a buried ancient landsurface, contributes to this rapid acidification by controlling the spatial and temporal movement of precipitation into the landsurface. As a result, the depth to which dissolved anthropogenic N as nitrate (NO3 ) is leached early in the winter wet season is limited to within the top 130 cm of soil where it accumulates and increases soil acidity.